Cultivation conditions and their impact on yerba mate ecophysiology and antioxidant potential - Gabriel Scherner Zanotto; André Luiz Montes; Luciana Bavaresco Andrade Touguinha; Wendel Paulo Silvestre; Cátia dos Santos Branco; Joséli Schwambach (Pesquisa Agropecuária Gaúcha)
This work aimed to evaluate the effect of light and shading on yerba mate's ecophysiology and antioxidant potential. To this end, an experiment was carried out in an entirely randomized design, with three treatments, being cultivated in full sun (Ts), in agroforestry (Ta), and in native forest (Tm). Photosynthesis activity and chlorophyll, phenolic compounds, flavonoids, and tannins  , and antioxidant activity were analyzed to determine the best cultivation environment that influences the ecophysiology and antioxidant potential of Yerba mate. Ts environment yielded higher concentrations of phenolic compounds, flavonoids, and tannins. Shaded environments showed greater antioxidant activity. Chlorophyll and photosynthesis indices differed in shaded environments, with Tm having higher concentration and photosynthetic activity and Ta having lower concentration and photosynthetic activity. The results show that PAR positively influenced the biochemical parameters. Shading was more efficient for antioxidant activity, and agroforestry contributed to greater antioxidant activity. The highest concentrations of chlorophyll and highest photosynthetic activity were found in yerba mate in native forests.